2021
DOI: 10.2147/ott.s278029
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Clinicopathological Characteristics of Stage I–III Colorectal Cancer Patients Deficient in Mismatch Repair Proteins

Abstract: Purpose To investigate the clinicopathological characteristics of stage I–III colorectal cancer (CRC) patients with deficient mismatch repair (dMMR) protein. Patients and Methods A retrospective analysis of 61 patients with stage I–III CRC confirmed by immunohistochemistry as dMMR after radical resection at Shenjing Hospital of China Medical University from May 2017 to June 2019 was performed. A total of 183 stage I–III CRC patients with proficient mismatch repair (pMMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Therefore, patients with early dMMR CRCs have a relatively better prognosis than pMMR patients in the same period. These data are roughly like the current research results of other scholars [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, patients with early dMMR CRCs have a relatively better prognosis than pMMR patients in the same period. These data are roughly like the current research results of other scholars [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…We also found a significant association of dMMR CRC with T4 stage, higher tumor grade, and mucinous differentiation, however, the association of dMMR CRC with younger age was not established in our study. Similarly, Liang et al [ 12 ] did not find any association of dMMR status with LVI, as noted in our study. Sacdalan et al [ 13 ] also reported aggressive histological features (poor differentiation, mucinous histology) of dMMR CRC in Filipino patients.…”
Section: Discussionsupporting
confidence: 89%
“…They found a significant association of dMMR status with age, gender, and tumor site, whereas no significant association was noted with T- and N-stages [ 11 ]. Conversely, Liang et al [ 12 ] in a study including 61 CRC patients concluded that there was a significant association of dMMR status with age (<55 years), female gender, location (right colon), tumor size (>5 cm), T-stage (T4), high grade, and mucinous differentiation. We also found a significant association of dMMR CRC with T4 stage, higher tumor grade, and mucinous differentiation, however, the association of dMMR CRC with younger age was not established in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Besides, CRCs with a higher rate of faulty mismatch repair (MMR) mechanisms have been reported to be associated with larger tumor diameter. 40 Since the mutations in the MSH3 gene, 1 of the 7 MMR genes in humans, has been suggested to play a role in tumor progression in CRCs, studies on this subject have reported that loss of MSH3 expression was associated with lymph node metastasis and distant metastasis in CRCs. 41 Our study revealed a significant association between the MSH3 mutation, for the prognostic value of which no consensus has yet been reached, and tumor diameter in CRCs.…”
Section: Discussionmentioning
confidence: 99%